Reframing, refining, and reconceptualising the worst forms of child labour through participatory adaptive programming - Apgar, Marina; Burns, Danny (Journal of modern slavery, 2021)
This article explores the potential of using participatory action research as an adaptive programming modality to drive learning and innovation to tackle the drivers of (and seek to eliminate) the Worst Forms of Child Labour. We draw on our experience from early phases of implementation of a large-scale action research programme, which despite the constraints covid-19 posed in moving to full implementation and participatory engagement with children and other stakeholders on the ground, is already generating rich learning about the opportunities and challenges of designing programmes that respond to the complex reality of WFCL. We share early learning about what it takes to be fully open to using the lived experience of programme development, and early findings from scoping and mapping of the dynamics of social norms, business practices and urban neighbourhoods and supply chains influencing WFCL in Bangladesh and Nepal, to frame and reframe the questions and response strategies and operationalise a participatory adaptive intent to work with hidden and complex dynamics that characterise the WFCL.

Finding and using causal hotspots: a practice in the making - Apgar, Marina; Snijder, Mieke (Institute of Development Studies, 2021)
This is the second blog in our series ‘Lessons on using Contribution Analysis for impact evaluation’. In our first blog, we introduced Contribution Analysis (CA) as an overarching approach to theory-based evaluation and the idea of causal hotpots as a way to zoom in, unpack and make the hard choices of where to focus evaluation research. Identifying specific links in the theory of change (ToC) with specific evaluation questions enables you to then choose appropriate methods. We have applied the approach in diverse settings, testing how robust Contribution Analysis can really be. Here we walk you through an example.

Learning through and about Contribution Analysis for impact evaluation - Apgar, Marina; Ton, Giel (Institute of Development Studies, 2021)
Over the past five years, colleagues from the Centre for Development Impact (CDI) – a joint initiative between the Institute of Development Studies, Itad and University of East Anglia – have been innovating with and learning how to use Contribution Analysis as an overarching approach to impact evaluation. In this blog series, we share our learning and insights, some of them in raw emergent form, highlight the complexities, nuances, excitements, and challenges of embracing new ways of doing impact evaluation. We begin this series by sharing ideas about ‘causal hotspots’ that first surfaced as ‘aha’ moments in our collaboration on the CDI short course Contribution Analysis for Impact Evaluation – the moments when we found the ways and words to better articulate our ideas and help people navigate the messy realities of theory-based evaluation.

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (Institute of Development Studies, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.